1985
DOI: 10.1172/jci112149
|View full text |Cite
|
Sign up to set email alerts
|

Activity in fetal bovine serum that stimulates erythroid colony formation in fetal mouse livers is insulinlike growth factor I.

Abstract: In the present study, the erythropoietic activity of fetal serum was characterized. Using fetal bovine serum (FBS) as a source of the erythropoietic activity and serum-free cultures of fetal mouse livers (FMLC assay) as a detection system, we found that FBS stimulated colony formation from late erythroid progenitor cells (CFU-E) in a dose-dependent fashion. The slope of the dose-response curve, however, was significantly different from that for erythropoietin (Ep), the best-characterized erythropoietic activit… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
30
1

Year Published

1987
1987
2007
2007

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(33 citation statements)
references
References 25 publications
2
30
1
Order By: Relevance
“…Earlier in vitro studies (3,4,(6)(7)(8)(9) lend support to speculations that the associations we observed indicate a causal relationship. In human cell cultures (6, 7) and in animal experiments (3-5, 8, 9), IGF-I stimulates erythropoietic colony and burst formations.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…Earlier in vitro studies (3,4,(6)(7)(8)(9) lend support to speculations that the associations we observed indicate a causal relationship. In human cell cultures (6, 7) and in animal experiments (3-5, 8, 9), IGF-I stimulates erythropoietic colony and burst formations.…”
Section: Discussionsupporting
confidence: 87%
“…The serum concentration of the major IGF-binding protein (IGFBP-3) reflects the total amount of IGF-I and IGF-I1 in the circulation and the secretion of growth hormone similarly or even better than the serum concentration of IGF-I alone (2). IGF-I has a role in the regulation of the erythropoietic system in vitro and also in vivo (3)(4)(5)(6)(7)(8)(9). IGF-I stimulates proliferation of murine and human erythroid progenitor cells in bone marrow culture systems (4,6).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…A 1% serum provides no more than 0 . 7 ng IGF-I per ml of medium (Kurtz et al 1985), which is five-to ten-fold lower than the ED50 of IGF-I on Sertoli cells as reported in several studies (Jaillard et al 1987, Rappaport & Smith 1995. Under our experimental conditions, we found that more than 85% of Sertoli cells were infected by lentivirus.…”
Section: Discussioncontrasting
confidence: 57%
“…For example, transforming growth factor-/3 and insulin-like growth factor I protect against several neurotoxic insults (Cheng and Mattson, 1992;Zhang et al, 1993;Prehn eta!., 1994;Singleton eta!., 1996). These factors may also be protective with respect to LPA because neurons are often cultured in medium supplemented with serum that contains LPA and other mediators, including transforming growth factor-/3 and insulin-like growth factor I (Kurtz et a!., 1985;Honegger and Humbel, 1986;Masui et a!., 1986;Eichholtz et al, 1993;Tokumura et a!., 1994;Moulin et al, 1997).…”
Section: Lpa Induces a Decrease In Mitochondrial Membrane Potentialmentioning
confidence: 99%